The analysis of adaptive reasoning ability reviewed from students’ confidence in ethnomathematic-based treffinger learning model - Fikriya, Annisa; Waluya, Stevanus Budi; Sunarmi, Sunarmi (Department of Mathematics, Universitas Negeri Semarang, 2018)
The objective of this study was to examine whether ethnomathematics-based Treffinger learning model was good to improve students’ adaptive reasoning ability and to describe the adaptive reasoning ability based on students’ self-confidence level. The method of this study was Mixed Methods. While the population of this study was tenth grade science students of Wiradesa High School academic year 2017/2018. Again, the population was divided into 2 categories, they were the tenth grade of Science 2 was the experimental class and the tenth grade Science 1 was a control class. Eventually, the result showed that: (1) Ethnomathematics-based Treffinger learning model has good quality in improving students' adaptive reasoning ability since the planning and the implementation of learning process had good criteria, starting from teacher’s and student’s activities and the average of learning outcomes had reached the minimum score (KKM) and (2) the classification of adaptive reasoning ability was based on students' confidence level.